Generation of a human induced pluripotent stem cell line (UNAMi001-A) from a Mexican patient with sporadic Parkinson’s disease - Flores-Ponce, Xóchitl; López-Ornelas, Adolfo; Escobedo-Avila, Itzel; Rodríguez-Violante, Mayela; Dávila-Ortiz de Montellano, David; Cervantes-Arriaga, Amín; Monroy-Jaramillo, Nancy; Velasco, Iván (Stem cell research, 2022)
Parkinson’s disease (PD) is a neurodegenerative disease caused by progressive loss of dopaminergic neurons in the substantia nigra pars compacta, which results in motor alterations. The exact mechanisms underlying the dopaminergic neurodegeneration in PD are still unknown. Here, we generated a human induced pluripotent stem cell (iPSC) line from dermal fibroblasts of a Mexican patient diagnosed with sporadic PD. The generated iPS cell line (UNAMi001-A) express pluripotency markers, maintain a normal karyotype and display the ability to differentiate into all three germ layers. This is the first iPSC line from a Mexican patient and will be useful for PD modeling.